FINANCIAL RISK MANAGEMENT STRATEGIES AND THE GROWTH OF MICROFINANCE SECTOR IN KENYA - Njuguna, Dr. James Rurigi; Gakure, Prof. Roselyn; Waititu, Dr. Anthony Gichuhi; Katuse, Dr. Paul (Journal of Accounting, 2017)
Purpose: The purpose of this study was to investigate how financial risk management strategies lead to growth of MFI sector in Kenya. Methodology: The study adopted a correlation survey research design. The population of this study was fifty seven (57) MFIs. The sampling frame was the list of MFIs provided in the AMFI website www.amfikenya.com. A sample of thirteen (17) MFIs was selected using the random sampling approach. A questionnaire and an interview schedule were the main data collection tools. Qualitative data was analyzed using content analysis whereas the quantitative data was analysed using Statistical Package for Social Sciences (SPSS) where descriptive and regression analysis were conducted to determine the relationship between enterprise risk management strategies and growth of MFIs. Findings: The findings indicated that MFIs had effective financial risk management strategies such as effective credit risk management practices, liquidity risk management practices, interest risk management practices and price risk management practices. In particular, MFIs took into consideration the conditions, characters, capacity, collateral and capital of borrowers. Strict debt collection practices were widely adopted by MFIs. In addition, the concept of Know Your Customer (KYC) policy, seem to have been adopted by MFIs. The relationship between financial risk management strategies and growth was positive and significant. It also shown that sources of funds for MFIs include external sources and internal sources and the most frequently used source of funds are bank loans. The use of banks loans may present various risk exposures to MFIs, the most significant being interest rate risk. However, the ability of MFIs to source funds from various sources indicates that MFIs can apply the pecking order by first exploiting internal sources of funds since they present a lower financial risks and then move on to external sources. However, despite the financial risk exposure accompanied by leverage from external sources, MFIs may also benefit as they may experience higher growth driven by the leverage. It was also found that MFIs had put in place a number of good practices that had emerged to promote responsible and inclusive lending. These include loan size limits, standardized (simple) loan terms, zero tolerance on delinquency, group-based lending. This finding implies that MFIs have put in place effective credit risk management policies which are part of an overall financial risk management strategy. The existence of effective financial risk management practices may have influenced the growth of MFIs Unique contribution to theory, practice and policy: The study recommends that the MFIs to continue practicing effective financial management practices as this would improve the growth of MFIs.